The Church’s Liturgical Idiom: Between Tradition and Modernity - HAGIU, Radu (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2025)
The liturgical language of the Orthodox Church stands at the crossroads of tradition and modernity, poised between reverence for inherited forms and the impulse toward renewal. This study seeks to transcend that polarity through the lens of Saint Sophrony of Essex’s notion of the liturgical idiom. Far from being a mere instrument of communication, liturgical language is portrayed as a vessel of divine energy – a manifestation of the creative power of the Logos. It constitutes a sacred, mystagogical register whose ultimate aim is not semantic clarity but communion with God. Within this framework, the question of intelligibility assumes a spiritual dimension: understanding arises not from linguistic simplicity but from the believer’s inward receptivity, as the idiom gestures toward realities that elude discursive thought. The argument unfolds through a reflection on the ontological status of divine names as verbal icons and on the anagogical, poetic vocation of liturgical utterance. In the end, the liturgical idiom emerges as a transformative mode of speech – one that elevates the soul, nurtures an unworldly ethos, and enables a genuine partaking in divine life, engaging the heart more profoundly than the intellect.